Spontaneous retroperitoneal bilious collection: A case report. Issue 4 (August 2022) - Moradi, Golnaz; Rezaei, Mohaddeseh; Miratashi Yazdi, Seyed A.
الملخص: الورم الصفراوي هو تراكم مغلف للصفراء في البطن. يأتي الورم الصفراوي بشكل عام بعد انفتاح القناة الصفراوية. كانت الحالة السريرية لهذا التقرير هي امرأة تبلغ من العمر 75 عاما تعاني من اليرقان والحمى وآلام في البطن والخمول وفقدان الشهية وقد تم إدخالها إلى قسم الطوارئ. أظهر "تصوير الطرق الصفراوية والبنكرياسية بالتنظير الداخلي بالطريق الراجع" تمددا شديدا منتشرا للقناة الصفراوية المشتركة والقناة الكبدية الشائعة مع عيوب الملء. تم استخراج حجر واحد وبعض الحمأة والقيح بعد الضرب بالبالون. تم إجراء وضع دعامة بلاستيكية للقناة الصفراوية المشتركة. أظهر الفحص بالموجات فوق الصوتية للبطن وجود حصوة في القناة الصفراوية المشتركة وتجمع سوائل في المنطقة المحيطة بالكلية. بتوجيه من الموجات فوق الصوتية، تم إدخال أنبوب تصريف داخل الورم الصفراوي خلف الصفاق. كشف الفحص بالموجات فوق الصوتية التسلسلية أن حجم الورم الصفراوي انخفض تدريجيا. يعتبر ثقب القناة الصفراوية الذي يتميز بتجمع السائل خلف الصفاق حالة نادرة للغاية ويمكن أن تكون قاتلة. تم استخدام التصوير بالموجات فوق الصوتية والتصوير المقطعي وتصوير الطرق الصفراوية والبنكرياسية بالتنظير الداخلي بالطريق الراجع لتشخيص الحالة. يشمل العلاج منع التسرب وتصريف الصفراء. Abstract: Biloma refers to the encapsulated accumulation of bile in the abdomen. Bilomas generally occur after bile duct disruption. The clinical case of the present report was a 75 Y/O woman with jaundice, fever, abdominal pain, lethargy, and anorexia who had been admitted to the emergency department. Endoscopic retrograde cholangiopancreatography (ERCP) showed severe diffuse dilation of the common bile duct (CBD) and common hepatic duct (CHD) with filling defects. One stone and some sludge and pus were extracted after balloon swiping. Plastic CBD stent placement was performed. An abdominal ultrasound scan showed a stone in the CBD and fluid collection in the right perirenal space. Under ultrasound guidance, a drainage tube was inserted into the retroperitoneal biloma. A serial ultrasound scan revealed a gradual decrease in the size of the biloma. Perforation of the bile duct, which is characterised by the collection of retroperitoneal fluid, is considered an extremely rare condition that can be fatal. Ultrasonography, computed tomography, and endoscopic retrograde cholangiopancreatography were used for the diagnosis. The treatment includes prevention of leakage and bile drainage.